Pengaruh Sistem Pengendalian Internal Pemerintahan dan Sistem Akuntansi Keuangan Daerah Pada Kantor Inspektorat Kota Padang Sumatera Barat - Nurfajriyati, Nurfajriyati; Muhammad Rivandi, (Jurnal Mutiara Ilmu Akuntansi, 2023)
This research aims to test the government's internal control system and regional financial accounting system on the effectiveness of regional financial management. Data collection for this research used a questionnaire. Questionnaires were delivered to 74 employees at the Padang City Inspectorate Office. This research is included in quantitative research. The sample was determined using total sampling technique. Data analysis uses multiple regression using SPSS 22 software. The results of this research show that the internal control system has no effect on the effectiveness of financial management and the accounting system has a positive effect on the effectiveness of financial management.